2016
DOI: 10.1039/c5cy01412c
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Ce(III,IV) ions for Bi in BiVO4 and its enhanced impact on visible light-driven photocatalytic activities

Abstract: The recombination of photogenerated charges can be greatly depressed by the charged crystal defects in the Bi1−xCexVO4+δ novel solid solution photocatalyst and both ˙OH and ˙O2− could be detected in the photoreaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 48 publications
4
35
0
2
Order By: Relevance
“…31,32 The crystallite size (d, nm) of Bi 1Àx Co x VO 4+d samples were evaluated from {121} peak of XRD patterns using the Scherrer's equation. 14,30 The d values of the Bi 1Àx Co x VO 4+d samples are presented in Table 1. As shown in Table 1, the crystallite size of Co-doped BiVO 4 slightly increased compared to that of bare BiVO 4 sample, implying that the presence of Co 2+ could inuence the formation of crystalline particles of BiVO 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 The crystallite size (d, nm) of Bi 1Àx Co x VO 4+d samples were evaluated from {121} peak of XRD patterns using the Scherrer's equation. 14,30 The d values of the Bi 1Àx Co x VO 4+d samples are presented in Table 1. As shown in Table 1, the crystallite size of Co-doped BiVO 4 slightly increased compared to that of bare BiVO 4 sample, implying that the presence of Co 2+ could inuence the formation of crystalline particles of BiVO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…5B. 13,30,40,41 The E g values of the Bi 1Àx Co x VO 4+d samples are presented in Table 1. Accordingly, the E g appeared to be slightly declining with increasing Co molar ratio.…”
Section: Optical Absorption Propertiesmentioning
confidence: 99%
“…In Figure 4 C, the V2p orbital exhibited splitting peaks at 516.80 and 522.65 eV, corresponding to the characteristic spin‐orbit split of V2p 1/2 and V2p 3/2 signals . These outcomes indicated that chemical states of Bi and V were 3+ and 5+, respectively . The O 1s spectra (Figure 4 C) of 0.5%‐Pd‐BVO samples at a binding energy (BE) of 529.7 eV could be deconvoluted into three pairs of individual components referring to the surface lattice oxygen (529.69 eV), the surface adsorbed oxygen species (530.62 eV), and water (531.96 eV) .…”
Section: Resultsmentioning
confidence: 98%
“…The photocatalytic efficiency of this material, however, is not as expected because of the recombination of the electron/hole (e – /h + ) pairs, which was caused by its weak surface adsorption and poor charge transport characteristics . Attempts to enhance the photocatalytic performance of BiVO 4 through restricting the recombination of the electron/hole (e – /h + ) pairs included the design of composites containing BiVO 4 , decoration of BiVO 4 by metals/oxides, the synthesis of BiVO 4 with surface Bi or O vacancy, and the fabrication of BiVO 4 with monoclinic‐tetragonal heterostructure ,. Among them, decoration of BiVO 4 by noble metals/oxides have been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Thus, to overcome these limitations and improve its quantum efficiency for OER application, various concepts have implemented. [41][42][43][44][45] Among them, the formation of heterostructures seems to be one of the most promising strategies. Using this strategy, the separation of charge carriers is maximized at the interface of two materials through carrier mobility alteration.…”
Section: Introductionmentioning
confidence: 99%